Analysis of the Implementation of Argument Driven Inquiry (ADI) in Students' Argumentation Skills - Annisa Setiawan; Jumadi Jumadi (Jurnal Penelitian Pendidikan IPA, 2023)
This study uses a literary study method using a type of qualitative research which aims to describe a suitable learning model to improve students' argumentation skills, namely the Argument Driven Inquiry (ADI) model because it requires students to learn independently to understand material concepts and practice directly. In the ADI model there is a syntax that the teacher can apply to students during science learning so that students are able to convey their arguments correctly and correctly based on existing material concepts. Because to face the challenges of 21st century education, skills such as thinking skills, analytical skills, and creativity skills are needed. Of the 56 articles found with similar topics, 13 were selected to obtain 13 articles which were analyzed to obtain the result that the existence of the Argument Driven Inquiry (ADI) model was able to improve students' argumentation abilities in the sense of students' ability to think critically in facing a problem or solving a problem, increasing students' understanding skills to the concept of science material presented by the teacher, and improve students' ability to practice directly in the environment so that they better understand events around them so as to be able to provide solutions in an argumentative manner related to theoretical science.Â